Effectiveness of Rescue Remedy in patients with light persistent asthma crisis - Marhyam Solano Pérez; Zulien Mercedes Cárdenas Godefoy; Pável Noel Blanco Figueredo; Nora Aida Pérez Fariñas; Gloria Esther Morell Hechavarria (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Edward Bach discovered floral therapy as a form of treatment that includes 39 floral essences, being Rescue Remedy one of the most used, which is related to emergency, stress and distress situations.   Objective: To evaluate the effectiveness of Rescue Remedy in patients with persistent mild asthma crisis.  Methods:  A study of therapeutic intervention was carried out in patients with persistent mild asthma crisis, assisted in the Emergency Department of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, during the third quarter of 2018. The sample was constituted by 60 patients, distributed in 2 groups with 30 members each one. The group A (study) was treated with floral therapy (Rescue Remedy) and group B (control) with medications.   Results: Before the 20 minutes of receiving the therapy, 90.0 % of the patients from group A improved the symptoms, unlike just 53.3 % of the patients from group B. None of the affected patients from the study group showed adverse reactions; while 96.7 % of the control group presented side effects.   Conclusions: The Remedy 39 or Rescue Remedy was effective as emergency therapy in the studied patients.